Alpha and Theta Oscillations Associated With Behavioral Phenotypes of Pain–Attention Interaction - Nikou Kelardashti; Benjamin T. Dunkley; Rima El‐Sayed; Vaidhehi Veena Sanmugananthan; Junseok Andrew Kim; Natalie Rae Osborne; Joshua C. Cheng; Anton Rogachov; Rachael L. Bosma; Ariana E. Besik; Karen Deborah Davis (Brain and Behavior)
ABSTRACT Purpose Pain is inherently salient and so draws our attention in addition to impacting performance on attention‐demanding tasks. Individual variability in pain–attention interactions can be assessed by two kinds of behavioral phenotypes that quantify how individuals prioritize pain versus attentional needs. The intrinsic attention to pain (IAP) measure quantifies the degree to which a person attends to pain (high‐IAP) or mind‐wanders away from pain (low‐IAP). The A/P categorization quantifies how pain impacts cognitive performance during an attention‐demanding task classifying individuals into P type (pain dominates, worse performance during pain in comparison to no pain) and A type (attention to task dominates, better performance during pain in comparison to no pain). Although previous MRI‐based studies have linked these phenotypes with the dynamic pain connectome (DPC), the underlying neural oscillations are not known. This paper aims to examine the brain–behavior relationship between alpha and theta oscillations within nodes of the DPC and pain–attention phenotypes. Method Fifty participants (27 F, 23 M) underwent resting‐state magnetoencephalography (MEG). Individual IAP scores were determined by assessing mind‐wandering during pain and A/P type was based on interference of pain with cognitive task performance. Finding The main findings were: (1) peak alpha frequency (PAF) power did not differ between low/high‐IAP individuals or A/P‐type individuals within the nodes of the DPC; (2) compared to high‐IAP individuals, those with low‐IAP have slower PAF in the left primary somatosensory cortex, posterior cingulate cortex and precuneus and higher theta power in the ascending nociceptive pathway and default mode network; (3) males with low‐IAP, compared to females, had higher PAF power throughout the DPC. Conclusion Alpha and theta oscillations within the DPC may underlie aspects of attentional focus and pain–attention interactions.